Uji Aktivitas Antibakteri Ekstrak Etanol Biji Nangka (Artocarpus Heterophyllus) Terhadap Bakteri Shigella Dysentriae dan Staphylococcus Epidermidis - Suharyanisa Suharyanisa; Jon Kenedy Marpaung; Julia Susanti (Inovasi Kesehatan Global, 2024)
Jackfruit seeds contain several secondary metabolites, including flavonoids, alkaloids, saponins, terpenoids, and steroids. The jackfruit tree is a tropical plant commonly found in Indonesia. This study aimed to determine whether extracts from jackfruit seeds have antibacterial activity against Shigella dysenteriae and Staphylococcus epidermidis. The antibacterial activity was tested using the discdiffusion method with concentrations of 10%, 15%, and 20%.The research results indicated that the diameter of the inhibition zone against Shigella dysenteriae at 10% concentration was 13.15 mm, at 15% concentration was 15.9 mm, and at 20% concentration was 19.08 mm. For Staphylococcus epidermidis, the inhibition zone diameters were 10.5 mm at 10% concentration, 13.1 mm at 15% concentration, and 13.7 mm at 20% concentration. The results demonstrated that as the concentration of ethanol extract from jackfruit seeds increased, the inhibition zones around the discs also increased. This was attributed to the varying volumes of ethanol extract present at each concentration level.It was found that the ethanol extract from jackfruit seeds exhibited strong inhibitory effects against both Shigella dysenteriae and Staphylococcus epidermidis bacteria.